On Belatedness. The Shaping of Portuguese Art History in Modern Times - Pinto dos Santos , Mariana (Artium Quaestiones, 2019)
Portuguese art history experienced remarkable development after World War II, especially with the work of José-Augusto França, who was responsible for establishing a historiographic canon for nineteenth- and twentieth-century Portuguese art that still endures. José-Augusto França developed a narrative that held Paris up as an artistic and cultural role model in relation to which he diagnosed a permanent delay in Portuguese art. This essay analyses França’s idea of belatedness in the context of Portuguese art historiography and political history and how it is part of a genealogy of intellectual thought produced in an imperial context, revisiting previous art historians and important authors, such as Antero de Quental and António Sérgio. Moreover, it aims to address how the concept of belatedness was associated with the idea of “civilisation” and the idea of “art as civilisation.” Belatedness also has implications in the constraints and specificities of writing a master narrative in a peripheral country – a need particularly felt in the second half of the twentieth century, to mark a political standpoint against the dictatorship that ruled from 1926 to 1974. Part of the reaction to fascism expressed the desire to follow other nations’ democratic example, but the self-deprecating judgements on Portuguese art were frequently associated with the identification of essentialist motifs – the “nature” of the Portuguese people, their way of thinking, of living, their lack of capacities or skills – and of a self-image of being “primitive” in comparison with other European countries that has antecedents going back to the eighteenth century. I will address the nostalgia for the empire and the prevailing notion of belatedness throughout the twentieth century regarding unsolved issues with that nostalgia.